IMPLEMENTASI PERATURAN PRESIDEN NOMOR 64 TAHUN 2020 PERUBAHAN ATAS PERATURAN PRESIDEN NOMOR 82 TAHUN 2018 TENTANG JAMINAN KESEHATAN TERAKIT IURAN BADAN PENYELENGGARA JAMINAN SOSIAL DI KOTA PEKANBARU - Ayu Tri Wulandari; Gusliana HB; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Article 29 of Presidential Regulation Number 64 of 2020 has alsobeen stipulated regarding the increase in BPJS Health contributions and theentry into force of the increase. As a result of the ongoing Covid-19 pandemicand, economic conditions have destroyed the national economy and reducedthe level of community welfare. The problem in this research is How is theImplementation of Presidential Regulation Number 64 of 2020 concerningHealth Insurance Related to the Increase in BPJS Contributions inPekanbaru City and What are the inhibiting factors in the implementation ofPresidential Regulation Number 64 of 2020 concerning Health InsuranceRelated to Increase in BPJS Contributions in Pekanbaru City: What are thecountermeasures in implementing Presidential Regulation Number 64 of2020 concerning Health Insurance Related to Increase in BPJS Contributionsin Pekanbaru City.And the results of this research can be concluded that PresidentialRegulation Number 64 of 2020 concerning Health Insurance Related to theIncrease in BPJS Contributions in Pekanbaru City has not been implementedproperly; The inhibiting factor in the implementation of presidentialregulation number 64 of 2020 concerning health insurance is related to thisincrease in contributions, namely causing an impact on BPJS Healthparticipants where the impact is on BPJS Health participants who arereluctant to pay BPJS Health contributions; Efforts have been made toimprove the provide services quickly which participants themselves can nowqueue online, namely without queuing for BPJS Health participants can do awebsite that has been provided by BPJS Health, BPJS Health participantsthemselves can participating in a break program in which BPJS Healthparticipants who are in arrears in making BPJS Health contributions canprovide valuables as collateral until the payment of the arrears is paid off.Keywords: Implementation, BPJS, Health